Clustering of Generation X and Generation Y Communities in Cybersecurity Using the K-Means Algorithm (Case Study of Depok City, West Java) - Wibowo, Adhitya Eka; Agung Triayudi (CV. Media Digital Publikasi Indonesia, 2024)
This research aims to explore the differences in understanding and awareness of cybersecurity between Generation X and Generation Y in Depok City, West Java. The K-Means algorithm is used to group communities based on characteristics relevant to cybersecurity. The results of the study show that there are significant differences in understanding and behavior related to cybersecurity between the two generations. Generation X tends to be more cautious in using technology and has a better knowledge of cybersecurity risks, while Generation Y is more proficient in using digital devices and applications but pays less attention to security aspects. Factors that affect the level of cybersecurity awareness in both generation groups include knowledge of cyber threats, education, and demographic factors. The findings of this research can help stakeholders in increasing awareness and knowledge about cybersecurity and developing better solutions to protect users from cyber threats